Eksistensi Partai Politik Lokal Aceh pada Pemilu 2024 - Havez Ababil; Abu Sahrin (Universitas Medan Area, 2026)
This study aims to analyze the existence of local political parties in Aceh in the 2024 general election and to identify the factors influencing their competitiveness against national political parties. The background of this research is rooted in the emergence of local political parties as a product of the 2005 Helsinki Memorandum of Understanding (MoU), which became the foundation for Aceh’s post-conflict political reconstruction. This study employs a qualitative method with a sociocultural approach, utilizing in-depth interviews and literature review. The findings reveal that local political parties continue to play a strategic role in representing Acehnese interests and sustaining post-conflict peace. However, their existence faces significant challenges, including declining electability, increasing competition with national parties, and internal fragmentation among local parties. Key factors affecting this condition include the performance of party cadres, campaign strategies, the influence of key figures (former GAM combatants, religious leaders, and civil actors), as well as the prevalence of money politics. Furthermore, the emergence of new religion-based local parties and the growing participation of young voters have reshaped the political landscape. This study concludes that the sustainability of local political parties in Aceh can no longer rely solely on historical legitimacy, but must be supported by institutional strengthening, cadre professionalism, and adaptability to the dynamics of modern politics.